Cerebral Microbleeds on Magnetic Resonance Imaging and Anticoagulant-Associated Intracerebral Hemorrhage Risk - Charidimou, Andreas; Shakeshaft, Clare; Werring, David J. (Frontiers in Neurology, 2012)
The increasing use of antithrombotic drugs in an ageing population (including anticoagulants to prevent future ischaemic stroke in individuals with atrial fibrillation) has been associated with a dramatic increase in the incidence of intracerebral haemorrhage (ICH) in users of antithrombotic drugs. Several lines of evidence suggest that cerebral small vessel disease (particularly sporadic cerebral amyloid angiopathy) is a risk factor for this rare but devastating complication of these commonly used treatments. Cerebral microbleeds (CMBs) have emerged as a key MRI marker of small vessel disease and a potentially powerful marker of future ICH risk, but adequately powered, high quality prospective studies of CMBs and ICH risk on anticoagulation are not available. Further data are urgently needed to determine how neuroimaging and other biomarkers may contribute to individualised risk prediction to make anticoagulation as safe and effective as possible. In this review we discuss the available evidence on cerebral small vessel disease and CMBs in the context of antithrombotic treatments, especially regarding their role as a predictor of future ICH risk after ischaemic stroke, where risk-benefit judgements can be a major challenge for physicians. We will focus on patients with atrial fibrillation because these are frequently treated with anticoagulation. We briefly describe the rationale and design of a new prospective observational inception cohort study (Clinical Relevance of Microbleeds in Stroke; CROMIS-2) which investigates the value of MRI markers of small vessel disease (including CMBs) and genetic factors in assessing the risk of oral anticoagulation-associated ICH.